An Analysis of Students Errors in Arranging Jumble Words into the Correct Sentences of the Eight Grade at SMP N 7 Padang - Syahmina Syahmina; Ainul Addinna (Journal of English Language Teaching, 2023)
The purpose of this research was to investigate proportion of omission and addition error and the sources of error made by students when arranging jumble words  at SMP N 7 Padang. The subject of this reserch was students of the eighth grade at SMP N 7 Padang. This research was conducted with quantitative methods and using test ang questionnaire as a tool of data collection. The results of this research show that students make more addition errors than omission errors. based on the research result, the percentage of omission error is 72,8% and addition error 27,2%. For the sources of error this researh focus on intralingual transfer and communication strategy, and the results of the questionnaire for intralingual transfer is 74,08% and communication strategy is 81,27% it means the most factor that makes students make errors in arranged jumble words test is intralingual transfer with percentage 74,08%The purpose of this research was to investigate proportion of omission and addition error and the sources of error made by students when arranging jumble words  at SMP N 7 Padang. The subject of this reserch was students of the eighth grade at SMP N 7 Padang. This research was conducted with quantitative methods and using test ang questionnaire as a tool of data collection. The results of this research show that students make more addition errors than omission errors. based on the research result, the percentage of omission error is 72,8% and addition error 27,2%. For the sources of error this researh focus on intralingual transfer and communication strategy, and the results of the questionnaire for intralingual transfer is 74,08% and communication strategy is 81,27% it means the most factor that makes students make errors in arranged jumble words test is intralingual transfer with percentage 74,08%